1995
DOI: 10.1073/pnas.92.6.2313
|View full text |Cite
|
Sign up to set email alerts
|

Alpha 1-antichymotrypsin regulates Alzheimer beta-amyloid peptide fibril formation.

Abstract: The major component of the cerebral plaques in Alzheimer disease is the j3-amyloid peptide, but serine proteinase inhibitors like cvl-antichymotrypsin (ACT) are also present. Their role in the pathogenesis of amyloid formation is unsettled. In addition to their function as proteinase inhibitors, serine proteinase inhibitors can interact with various hydrophobic compounds, a reaction accompanied by a transition from the stressed to the relaxed conformation. We report here on the ability of ACT to regulate the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
80
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(81 citation statements)
references
References 26 publications
1
80
0
Order By: Relevance
“…125,130 This ability to interact with a variety of molecules presents a difficulty when attempting to measure Ab levels in biological fluids as the antigenic epitopes may be masked by these bound molecules. 131,132 The interaction of Ab with these binding proteins has been shown to modulate the formation of Ab fibrils 127,128,130 and the binding of Ab complexes to the LRP-1 receptor. Therefore, plasma Ab-binding proteins may have a dual function by reducing the formation of toxic oligomers and fibrils and by enhancing the clearance and degradation of Ab peptides through LRP-1-mediated endocytosis.…”
Section: Ab-binding Proteins In Blood Plasmamentioning
confidence: 99%
See 1 more Smart Citation
“…125,130 This ability to interact with a variety of molecules presents a difficulty when attempting to measure Ab levels in biological fluids as the antigenic epitopes may be masked by these bound molecules. 131,132 The interaction of Ab with these binding proteins has been shown to modulate the formation of Ab fibrils 127,128,130 and the binding of Ab complexes to the LRP-1 receptor. Therefore, plasma Ab-binding proteins may have a dual function by reducing the formation of toxic oligomers and fibrils and by enhancing the clearance and degradation of Ab peptides through LRP-1-mediated endocytosis.…”
Section: Ab-binding Proteins In Blood Plasmamentioning
confidence: 99%
“…The nature of the Ab peptide gives it the capacity to interact with a variety of plasma proteins including albumin, 125 a2M, 126,127 a1-antichymotrypsin (ACT), 128 serum amyloid P component (SAP), 129 complement proteins, transthyretin, apoferritin, apolipoproteins and lipoproteins. 125,130 This ability to interact with a variety of molecules presents a difficulty when attempting to measure Ab levels in biological fluids as the antigenic epitopes may be masked by these bound molecules.…”
Section: Ab-binding Proteins In Blood Plasmamentioning
confidence: 99%
“…For example, ␣ 1 -antichymotrypsin, when incubated with A␤ peptides at ratios lower than 1:100, accelerates A␤ fibrillation (36). However, when the ␣ 1 -antichymotrypsin to A␤1-40 ratio is raised to 1:10, fibril formation is inhibited (37). Apoliprotein E4 (Apo E4) is another example in which fibrillation of A␤ peptide is both inhibited and accelerated.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, previous studies have suggested that a1-antichymotrypsin can either promote (Ma et al, 1994) or inhibit (Fraser et al, 1993;Eriksson et al, 1995) A/I amyloid fibril assembly. Our findings indicated that cr1-antichymotrypsin was a good inhibitor of A/I (1-40) fibril formation.…”
Section: Discussionmentioning
confidence: 99%